Salinity threshold of desalinated saline water used for drip irrigating: The perspective of emitter clogging. (10th August 2022) - Liu, Zeyuan; Hou, Peng; Zha, Yingdong; Muhammad, Tahir; Li, Yunkai
Abstract: High energy consumption of desalinated saline water (DSW) caused a bottleneck, hindering the application of DSW drip irrigation in agriculture. In fact, the appropriate salinity level for agriculture drip irrigation could be much higher than potable water. Therefore, new desalination technology (e.g. capacitive deionization, blended desalinated water), owing its low energy consumption and meet the target salinity threshold removal according to crop requirements, has attracted extensive attentions. However, the DSW target salinity threshold may drastically increase the risk of emitter clogging, and reduce the operational performance of drip irrigation systems. Thus, this study assessed the DSW salinity threshold from the perspective of emitter clogging. The results suggested that the DSW salinity threshold should be kept below 5 g/L to maintain the favorable anti-clogging performance of drip irrigation. Emitter clogging was increased gradually between the salinity 1–5 g/L, while, sharped increase was observed at salinity above 5 g/L. Compared with 5 g/L, the treatments 7–9 g/L, significantly increased calcium fouling (12.5–26.4 mg/cm −2 ) and silica fouling (5.3–11.9 mg/cm −2 ), which could be attributed to, the rapid increase of calcium sulfate and calcium phosphate, and the key water quality parameter i.e. Ca 2+ and Mg 2+ concentrations, which greatly enhance the flocculation between silica particles and accelerated the polymerization of silicon. Furthermore, 7–9 g/L treatments aggravated the synergistic interactions among calcium fouling and silica fouling. Overall, these findings would provide a new perspective for DSW salinity threshold selection, with potential implications for sustainable development of agriculture water desalination. Graphical abstract: Image 1 Highlights: The desalinated saline water (DSW) of salinity threshold should be kept below 5 g/L. The emitter anti-clogging capacity decreased sharply as DSW salinity above 5 g/L. Clarify the influence path of DSW salinity on calcium-silica fouling.